PENGARUH EKSTRAK CHANNA STRIATUS TERHADAP KADAR DHA SERUM DAN NIHSS PASIEN STROKE ISKEMIK AKUT - Kundha Deyanningtyas; Retnaningsih Retnaningsih; Amin Husni (PERDOSNI, 2018)
THE EFFECT OF CHANNA STRIATUS EXTRACT ON DHA SERUM LEVELS AND NIHSS IN ACUTE ISCHEMIC STROKE PATIENTSABSTRACTIntroduction: The level of docosahexanoic acid (DHA) is associated with clinical outcome in acute ischemic stroke (AIS). Channa striatus/snakehead fish has a neuroprotective function due to its DHA content.Aims: Investigate the effect of Channa Striatus extract (EIG) administration which contains DHA on DHA serum levels and neurological clinical output of AIS patients.Methods: This was a randomized pre-posttest control group design with double-blind study. Patients were divided into two groups: treatment, with additional 15 grams EIG administered for 7 days, and control, without additional EIG. DHA serum levels and NIHSS scores were measured before and after treatment. Other factors that may affected the out- come were also analyzed by multivariate statistic.Result: A total of 42 subjects were allocated randomly as treatment or control. The difference of elevated DHA se- rum levels in treatment group was significantly greater than control group. There was a negative correlation between DHA serum levels changes and NIHSS changes. Multivariate analysis showed that NIHSS improvement was affected by EIG (Odds ratio/OD:0.25) gender (OR:5.64).Discussions: There was a significant relationship between EIG supplementation with NIHSS changes. EIG may im- prove neurologic clinical outcome a one-fourth times greater than placebo, thus can be considered as supportive treatment in the recovery of acute ischemic stroke patients.Keywords: Channa Striatus, docosahexaenoic acid (DHA), ischemic stroke, NIHSSABSTRAKPendahuluan: Kadar docosahexanoic acid (DHA) berkaitan dengan luaran klinis stroke iskemik akut (SIA). Channa Striatus/ikan gabus mempunyai fungsi neuroprotektif karena memiliki kandungan DHA.Tujuan: Mengetahui pengaruh pemberian ekstrak ikan gabus (EIG) yang mengandung DHA terhadap kadar DHA serum serta luaran klinis pasien stroke iskemik akut.Metode: Penelitian dengan desain randomized pre-posttest control group secara tersamar ganda. Pasien dibagi menjadi 2 kelompok; kelompok perlakuan mendapatkan EIG 15gr selama 7 hari dan kelompok kontrol tanpa perlakuan tambahan. Kadar DHA serum dan skor NIHSS diukur sebelum dan sesudah perlakuan. Faktor-faktor lain yang berpengaruh pada luaran klinis juga dianalisis secara multivariat.Hasil: Sebanyak 42 subjek dilakukan random alokasi sebagai kelompok perlakuan atau kontrol. Didapatkan adanya selisih peningkatan kadar DHA serum pada kelompok perlakuan yang lebih besar secara bermakna dibanding kelompok kontrol. Terdapat korelasi negatif antara perubahan kadar DHA serum dengan perubahan skor NIHSS. Analisis multivariat tampak bahwa EIG berpengaruh pada penurunan skor NIHSS (rasio Odds/RO:0,25) dan variabel jenis kelamin (RO:5,64).Diskusi: Terdapat hubungan yang bermakna antara pemberian EIG dengan perubahan skor NIHSS pasien stroke iskemik akut. Pemberian EIG dapat memperbaiki luaran klinis neurologis seperempat kali lebih besar dibanding plasebo, sehingga dapat dipertimbangkan untuk penunjang pemulihan pasien stroke iskemik akut.Kata kunci: Channa Striatus, docosahexaenoic acid (DHA), NIHSS, stroke iskemik